Chemistry does general relativity: reaction-diffusion waves can model gravitational lensing - Cohen-Cobos, Daniel; Sanders, Kiyomi; DeGroot, Laura; Guarnera, Heather; Leary, Cody; Lindner, John F.; Manz, Niklas (Frontiers in Physics, 2024)
Gravitational lensing is a general relativistic (GR) phenomenon where a massive object redirects light, deflecting, magnifying, and sometimes multiplying its source. We use reaction-diffusion (RD) Belousov-Zhabotinsky (BZ) chemistry to study this astronomical effect in a table-top experiment. We experimentally observe BZ waves passing through non-planar, quasi-two-dimensional molds and reproduce the waveforms in computer simulations using planar RD waves propagating with variable diffusion. We tune the variable diffusion to match the Schwarzschild-coordinate light speed near a spherical mass so the RD propagation approximates Einstein’s famous light deflection relation. We discuss varying the diffusion or reaction rates with a gel matrix or with illumination, electric field, or temperature gradients.